Analisis Penegakan Hukum Terhadap Jaringan Narkotika dan Obat-Obatan Terlarang di Kalangan Pelajar Melalui Media Sosial di Bandar Lampung - Satrio Nur Hadi; Dwi Nurahman; Dian Herlambang (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Currently, the rate of narcotics crime cases among students has increased every year. Because there are many new methods used by narcotics traffickers to sell and distribute illegal drugs to teenagers and students. Starting from inviting and teaching students who are originally users to participate in selling these illegal drugs in the student environment and creating a sales network for narcotics and illegal drugs between students and also even creating WhatsApp groups and other social media that are used for transactions of these illicit goods. . There have been many efforts and actions taken by the police and the National Narcotics Agency (BNN) to follow up and deal with this matter, starting from preventive or prevention efforts and repressive efforts or actions in accordance with applicable legal regulations. Prevention or prevention efforts have been carried out through outreach efforts about the dangers of narcotics and illegal drugs to students in the school environment and the community. And repressive efforts were carried out by taking firm legal action through arresting narcotics dealers and raids at entertainment venues and in fact there were several minors or students of student age who were caught carrying narcotics and illegal drugs. The problem in this research is what are the efforts of law enforcement officials in tackling criminal acts of narcotics and illegal drug abuse among students, and what are the inhibiting factors in tackling narcotics crimes among these students. It is hoped that this research can become reference material and literature in following up and tackling criminal acts of narcotics trafficking among students in Bandar Lampung which is increasingly worrying.